A SYSTEMATIC LITERATURE REVIEW ON AUTOMATIC COMPUTER AIDED PROCESS PLANNING - Rosianu, Sergiu; Oancea, Gheorghe (ACTA TECHNICA NAPOCENSIS Series: Applied Mathematics, Mechanics, and Engineering, 2024)
Manufacturing industries are facing challenging times influenced by the trends of automatization and digitalization. Industry 5.0, in Europe and other concepts implemented in other parts of the world, is defining specific guidelines for a more humancentric approach. The implementation of artificial intelligence models has been increased in different areas. In this article, using the systematic literature review methodology, the development of solutions for the Automatic Computer Aided Process Planning are analyzed. Different concepts, like Automatic Feature Recognition or the Multi Sectional Views, are being compared, to find and highlight the actual research potential. Using some evaluation criteria, the relevance of all discovered solutions is described, having in view the impact on human centricity.
Keywords: Systematic Literature Review; Automatic Computer Aided Process Planning; Automatic Feature Recognition; Manufacturing process planning optimization; Computer Aided Design